A Framework For Deployment Of Process Improvement For Manufacturing Industry - Loh , Chee Keong (2011)
Owing to growing competitiveness in the market and year-on-year price reduction that is highly demanded by consumers, many companies in manufacturing industry have to embark on process improvement. The implementation of process improvement in manufacturing industry will improve the efficiency of existing operation process and yield high profit to the company. However, due to lack of knowledge and capability to perform process improvement, many companies fail to gain the maximum benefit from their own process improvement. Therefore, to ensure the implementer especially new practitioner can effectively embark in the process improvement, a new framework named DRIES (Define, Review, Identify, Execute, and Sustain) is developed in this research.